(untitled) (Ajudikasi : Jurnal Ilmu Hukum, 2022)
In its development, the recognized legal families to date are the Romano-Germanic legal family, the common law family and the family of socialist law. Based on the three legal families, which legal family belongs to the Indonesian criminal law system. The purpose of this research is to find out which legal family belongs to the Indonesian criminal law system. The type of research used is normative juridical law research conducted using legal materials that focus on positive legal norms, consisting of secondary data as primary data and primary data as supporting data. The results of the studies that have been carried out show that the Indonesian criminal law system belongs to the Romano-Germanic legal family. This can be seen from the existence of identical characteristics, namely the use of statutory regulations as the main source of law in the form of a book and there is a codification system. Furthermore, based on a comparison with the Dutch criminal law system, several similarities were found, namely that the two countries base their criminal law on law.